Pelaksanaan Peraturan Bupati Badung Nomor 38 Tahun 2018 Dalam Pemberian Bantuan Perlindungan Sosial Bagi Para Lanjut Usia Di Kabupaten Badung - I Ketut Sukadana; Desak Gede Dwi Arini; Dhiananda Ningrat (Jurnal Konstruksi Hukum, 2020)
In order to realize a decent and beneficial life, and fulfill the rights to the basic needs of society in order to achieve social welfare for the elderly of the Badung Regency Government through the social Service provides social protection assistance to the elderly in Badung regency which is carried out in a directional, planned and sustainable. Distribution of social compensation to the elderly with the issuance of the rule of Badung Regent Number 38 year 2018 about social protection assistance Elderly. Compensation for elderly people of Badung regency at the launching of the PEAK of the anniversary Mangupura to 9 which fell on November 16, 2018. The issue of problems used in this research is:(1) How to exercise in the provision of social protection for elderly in Badung Regency;(2)what is the inhibitory factor in the provision of elderly social protection assistance in Badung regency. This study was conducted using empiricallegal research. Data and data sources of This research is a primer that is through field research and secondary material writing experts and the results of scientists are then processed and analyzed descriptively to get a conclusion. Based on the results of the study, it can be concluded that the implementation of the continued assistance of age aims to provide social assistance for the elderly in the Badung Regency, that the barriers faced by social services in the distribution of social assistance due to not synchronicity the data in the village/Kelurahan with data existing in the social service of Badung Regency. The advice given by the author is expected to have the ation between the logging conducted by the village apparatus/Kelurahan related to the number of elderly who have each region so that the social allowances can be shared evenly and precisely the target so that the aid is delivered appropriately.